Implementasi Digital Marketing Sebagai Media Pemasaran untuk Meningkatkan Omset UMKM di Tenun Lurik Bagong Asli Kedungjambal, Tawangsari, Sukoharjo - Erlinawati, Mira; Muhtarom, Moh; Nugroho, Novemy Triyandari; Nur'aini, Citra Ayu; Aurora, Cindy Nasywa (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The development of MSMEs in Indonesia continues to improve in quality, supported by strong government initiatives that help maintain and strengthen the national economic structure. However, partners still face key challenges, particularly in marketing and business management. They have no media or online platforms to promote their authentic Kedungjambal Lurik Bagong fabric products, and the absence of a legal business entity reduces consumer trust. Effective management is also needed to organize resources and achieve business goals efficiently. To overcome these issues, the PKM program aims to implement digital marketing strategies through the creation of a website, business Instagram, and WhatsApp Business accounts for product promotion and sales. Partners receive training to operate these platforms independently. Furthermore, the PKM team assists in registering a business entity (CV) and obtaining copyright for the Lurik fabric design, thereby improving product credibility, expanding market access, and increasing the competitiveness of the MSME.